Protection for Sale under Monopolistic Competition - Chang, Pao Li (Institutional Knowledge at Singapore Management University, 2005)
This paper proposes a general empirical framework to estimate the protection-for-sale model, where the protection regime shifts according to a sector's market structure (perfectly or monop-olistically competitive). We base the protection structure on Grossman and Helpman (1994) for the subset of perfectly competitive sectors and on Chang (2005) for the subset of monop- olistically competitive sectors. The two protection regimes are simultaneously estimated with joint constraints. The results of the J-test consistently reject the homogeneous (perfect compe- tition) protection-for-sale model often adopted in previous literature and suggest a direction of improvement toward the proposed heterogeneous protection structure model.